2013
DOI: 10.4048/jbc.2013.16.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Finding of Breast Cancer Cases and in Their First-Degree Relatives

Abstract: PurposeThe aim of this study was to evaluate and compare the rate of sister chromatid exchange (SCE), the occurrence of micronuclei, and the lymphocyte proliferation rate index (PRI) in patients with breast cancer, their first-degree relatives, and healthy volunteers.MethodsWe analyzed the frequency of SCE and micronuclei, and the PRI in the peripheral blood lymphocytes of 30 women with breast cancer, 22 of their female family members, and 20 age-matched healthy female volunteers.ResultsSCE occurred significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…In the present study, the extent of spontaneous chromosome damage in lymphocytes of BC patients and control subjects was examined. Basal levels of DNA damage in peripheral lymphocytes of untreated BC patients have been described previously (Cefle et al, 2006;Kopjar et al, 2007;Aristei et al, 2009;Santos et al, 2010;Çelik et al, 2013). In these studies, such damage was found to be significantly higher in BC patients than in control subjects.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, the extent of spontaneous chromosome damage in lymphocytes of BC patients and control subjects was examined. Basal levels of DNA damage in peripheral lymphocytes of untreated BC patients have been described previously (Cefle et al, 2006;Kopjar et al, 2007;Aristei et al, 2009;Santos et al, 2010;Çelik et al, 2013). In these studies, such damage was found to be significantly higher in BC patients than in control subjects.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, a significant increase in the frequency of SCE was observed in familial compared to sporadic patients, hypothesizing an increased genome susceptibility as previously reported (13). However, in our series of BC patients, we found an SCE frequency lower than that of other studies (13,21). We believe that the frequency of SCE of the BC patients from the Apulia Caucasian population is different than that in other populations.…”
Section: Familial N=22contrasting
confidence: 53%
“…This appears to be a direct consequence of the failure to form a nuclear envelope gap, blocking the acentric chromosome from entering the daughter telophase nucleus. Historically, micronuclei have been used as biomarkers for genomic instability, and their increased presence of micronuclei in human cells is typically associated with cancer ( Bonassi et al ., 2011 ; Santos et al ., 2010 ; Celik et al ., 2013 ). As such, there has been much interest in understanding the cellular response to micronucleus formation and subsequent micronucleus fate ( Fenech et al ., 2011 ; Huang et al ., 2011 ; Kirsch-Volders et al ., 2011 ; Hatch et al ., 2013 ; Ji et al ., 2013 ).…”
Section: Discussionmentioning
confidence: 99%